A quantitative evaluation of indoor environmental quality in refurbished kindergarten buildings: A Malaysian case study. (December 2015) - Salleh, Naziah Muhamad; Kamaruzzaman, Syahrul Nizam; Riley, Mike; Ahmad Zawawi, Emma Marinie; Sulaiman, Raha
Abstract: In Malaysia, the coverage of kindergarten education has improved dramatically in recent times, although many kindergartens are located in buildings that were not originally designed for that purpose. Indoor Environmental Quality (IEQ) is considered to be one of the most important factors affecting the physical development of children. Hence, it is essential to evaluate the indoor conditions of those kindergartens which are based in buildings that have been refurbished and adapted from their original purpose. It is posited that such refurbished environments provide sub-optimal IEQ for kindergarten use, which is reflected in user perception and satisfaction. This study presents the results of the IEQ investigations conducted in refurbished kindergarten buildings in Malaysia with the focus on identifying occupants' satisfaction with the various IEQ factors. The researchers aim to utilize the results of this work to develop a benchmark for analogous studies. 240 refurbished kindergarten buildings in Malaysia were studied to evaluate occupants' perceptions and levels of satisfaction. The results indicate that the occupants found Air Movement, Ventilation, and Freshness to be of a poor quality due to the high occupancy density. Noise was the least satisfactory IEQ factor due to the closeness of the kindergartens to main roads (external noise), as well as the small size of classrooms (internal noise). It was found that Colour and Attractiveness are the most important IEQ factors from the occupants' viewpoint. This study provides a practical benchmark for the conversion of buildings' usage. Highlights: IEQ is the factors affecting the physical development of children. "Air Movement", "Ventilation", and "Freshness" scored poor quality. "Colour" and "Attractiveness" are the most important IEQ factors. "Noise" factor is the least satisfactory IEQ factor.